Moderate gains in total yield but large shifts in yield partitioning due to trait variations in a cereal/legume intercropping system: A modelling approach - Dereje T. Demie; Tjeerd Jan Stomph; Thomas F. Döring; Gunther Krauss; Thomas Gaiser; Frank Ewert; Ixchel M. Hernández-Ochoa; Wopke van der Werf; Sabine J. Seidel (Field Crops Research, 2026)

Corrigendum to “The overlooked effects of environmental impacts on root:shoot ratio in experiments and soil-crop models” [Sci. Total Environ. 955 (2024) 176738] - S.J. Seidel; S.H. Ahmadi; L. Weihermüller; A. Couëdel; G. Lopez; D. Behrend; B. Kamali; T. Gaiser; I.M. Hernández-Ochoa (Science of The Total Environment, 2026)

Wheat crop models underestimate drought stress in semi-arid and Mediterranean environments - H. Webber; D. Cooke; C. Wang; S. Asseng; P. Martre; F. Ewert; B. Kimball; G. Hoogenboom; S. Evett; A. Chanzy; S. Garrigues; A. Olioso; et al. (Field Crops Research, 2025)

Winter wheat shoot and root phenotypic plasticity under fertilized and nutrient-deficient field conditions - G. Lopez; S. Hadir; S.D. Mouratidis; M.A. Shuva; H. Hüging; S.L. Bauke; T. Gaiser; G. Schaaf; S.J. Seidel (European Journal of Agronomy, 2025)

Robust species-optima estimates from non-uniformly sampled environmental gradients - Kelsey J. Solomon; R. Jan Stevenson; Donatto Surratt; Kevin R. T. Whelan; Franco A. C. Tobias; Katherine M. Johnson; Evelyn E. Gaiser (Journal of Paleolimnology, 2025)
Abundance-weighted averaging is a simple and common method for estimating taxon preferences (optima) for phosphorus (P) and other environmental drivers of freshwater-ecosystem health. These optima can then be used to develop transfer functions to infer current and/or past environmental conditions of aquatic ecosystems in water-quality assessments and/or paleolimnological studies. However, estimates of species’ environmental preferences are influenced by the sample distribution and length of environmental gradients, which can differ between datasets used to develop and apply a transfer function. Here, we introduce a subsampling method to ensure a uniform and comparable distribution of samples along a P gradient in two similar ecosystems: the Everglades Protection Areas (EPA) and Big Cypress National Preserve (BICY) in South Florida, USA. Diatom optima were estimated for both wetlands using weighted averaging of untransformed and log-transformed periphyton mat total phosphorus (mat TP) values from the original datasets. We compared these estimates to those derived from random subsets of the original datasets. These subsets, referred to as “SUD” datasets, were created to ensure a uniform distribution of mat TP values along the gradient (both untransformed and log-transformed). We found that diatom assemblages in BICY and EPA were similar, dominated by taxa indicating oligotrophic conditions, and strongly influenced by P gradients. However, the original BICY datasets contained more samples with elevated mat TP concentrations than the EPA datasets, introducing a mathematical bias and resulting in a higher abundance of taxa with high mat TP optima in BICY. The weighted averaged mat TP optima of BICY and EPA taxa were positively correlated across all four dataset types, with taxa optima of SUD datasets exhibiting higher correlations than in the original datasets. Equalizing the mat TP sample distribution in the two datasets confirmed consistent mat TP estimates for diatom taxa between the two wetland complexes and improved transfer-function performance. Our findings suggest that diatom environmental preferences may be more reliable across regional scales than previously suggested and support the application of models developed in one region to another nearby region if environmental gradient lengths are equalized and data distribution along gradients is uniform.

Resource acquisition and interactions in spring wheat/faba bean intercropping under diverse environments - Dereje T. Demie; Sabine J. Seidel; Daniel Wallach; Thomas F. Döring; Frank Ewert; Thomas Gaiser; Madhuri Paul; Ixchel M. Hernández-Ochoa (Field Crops Research, 2025)

Evaluating a new intercrop model for capturing mixture effects with an extensive intercrop dataset - Dereje T. Demie; Daniel Wallach; Thomas F. Döring; Frank Ewert; Thomas Gaiser; Sofia Hadir; Gunther Krauss; Madhuri Paul; Ixchel M. Hernández-Ochoa; Rémi Vezy; Sabine J. Seidel (Agriculture, Ecosystems & Environment, 2025)

Correction to: Root growth and belowground interactions in spring wheat /faba bean intercrops - Sofia Hadir; Thomas F. Döring; Eric Justes; Dereje T. Demie; Madhuri Paul; Nicole Legner; Roman Kemper; Thomas Gaiser; Odette Weedon; Frank Ewert; Sabine J. Seidel (Plant and Soil, 2025)

Root growth and belowground interactions in spring wheat /faba bean intercrops - Sofia Hadir; Thomas F. Döring; Eric Justes; Dereje T. Demie; Madhuri Paul; Nicole Legner; Roman Kemper; Thomas Gaiser; Odette Weedon; Frank Ewert; Sabine J. Seidel (Plant and Soil, 2025)
Background and aims Intercrops offer multiple advantages over sole crops. The aim of our study was to characterize root growth and interactions in spring wheat/faba bean intercrops to better understand belowground interactions that govern resource capture. Materials and methods A field experiment was conducted with one faba bean cultivar and two spring wheat cultivars sown at three sowing densities, defining three intercropping designs. Destructive root coring was conducted (0–100 cm) in the intercrops and sole crops at two development stages. FTIR spectroscopy was used to discriminate the species’ root masses. The plant-plant interaction index was calculated to represent the belowground interactions. Results A negative impact of intercropping on total root mass was observed in the treatment with high sowing density in both stages. For the fully and partial replacement design treatments, plant-plant facilitation was more pronounced than competition in all layers. Competition dominated root growth in the treatment with high sowing density in both stages. Lower sowing densities encouraged deep root growth of wheat (both cultivars) in intercropping. The early root growth in depth and in density of one spring wheat cultivar impacted negatively faba bean root growth. Intercropping resulted in a grain yield advantage in both fully and only one partial replacement design treatment. Conclusion In the intercrops, total root mass and plant-plant interactions were affected more by sowing density than by the spring wheat cultivar. Understanding the effect of sowing density on root growth in intercropping can help to support the design of sustainable intercropping systems.

The overlooked effects of environmental impacts on root:shoot ratio in experiments and soil-crop models - S.J. Seidel; S.H. Ahmadi; L. Weihermüller; A. Couëdel; G. Lopez; D. Behrend; B. Kamali; T. Gaiser; I.M. Hernández-Ochoa (Science of The Total Environment, 2024)

Assessing the impact on crop modelling of multi- and uni-variate climate model bias adjustments - S. Galmarini; E. Solazzo; R. Ferrise; A. Kumar Srivastava; M. Ahmed; S. Asseng; A.J. Cannon; F. Dentener; G. De Sanctis; T. Gaiser; Y. Gao; S. Gayler; et al. (Agricultural Systems, 2024)

Experimental Saltwater Intrusion Drives Rapid Soil Elevation and Carbon Loss in Freshwater and Brackish Everglades Marshes - Sean P. Charles; John S. Kominoski; Tiffany G. Troxler; Evelyn E. Gaiser; Shelby Servais; Benjamin J. Wilson; Stephen E. Davis; Fred H. Sklar; Carlos Coronado-Molina; Christopher J. Madden; Steve Kelly; David T. Rudnick (Estuaries and Coasts, 2019)

Functional and Compositional Responses of Periphyton Mats to Simulated Saltwater Intrusion in the Southern Everglades - Viviana Mazzei; Evelyn E. Gaiser; John S. Kominoski; Benjamin J. Wilson; Shelby Servais; Laura Bauman; Stephen E. Davis; Steve Kelly; Fred H. Sklar; David T. Rudnick; Jemma Stachelek; Tiffany G. Troxler (Estuaries and Coasts, 2018)

Adaptation of crop production to climate change by crop substitution - E. Eyshi Rezaei; T. Gaiser; S. Siebert; F. Ewert (Mitigation and Adaptation Strategies for Global Change, 2015)

Wetland Ecosystem Response to Hydrologic Restoration and Management: The Everglades and its Urban-Agricultural Boundary (FL, USA) - Pamela L. Sullivan; Evelyn E. Gaiser; Donatto Surratt; David T. Rudnick; Stephen E. Davis; Fred H. Sklar (Wetlands, 2014)

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

Paleoenvironmental change in wetlands of the Florida Everglades, southeast USA - William T. Anderson; Evelyn E. Gaiser (Journal of Paleolimnology, 2013)

Changes in soil organic carbon fractions in a tropical Acrisol as influenced by the addition of different residue materials - Thomas Gaiser; Karl Stahr; Marc Bernard; Biau T. Kang (Agroforestry Systems, 2012)

Spatial and temporal distributions of epiphytic diatoms growing on Thalassia testudinum Banks ex König: relationships to water quality - T. A. Frankovich; E. E. Gaiser; J. C. Zieman; A. H. Wachnicka (Hydrobiologia, 2006)

Water use efficiency of a maize/cowpea intercrop on a highly acidic tropical soil as affected by liming and fertilizer application - T. Gaiser; I. de Barros; F.-M. Lange; J.R. Williams (Plant and Soil, 2004)